Nutrient dynamics under unmanaged rubber, cocoa, and oil palm plantations in a sandy soil under humid lowland tropical climatic conditions - Bob, Joel; Michael, Patrick S. (International Journal of Environment, 2022)
Changes in land use are an important issue in many farms that affect soil biological, chemical, and physical properties temporarily under cropping cycles or when the land is permanently allocated to perennial tree crops, e.g., in agroforestry. This study investigated the changes in sandy soil chemistry induced by three perennial tree crops (rubber, cocoa, and oil palm) growing in 30-year-old unmanaged and abandoned plantations and the surrounding grasslands dominated by cogon grass. A disruptive approach was used to collect soil samples from the top 60 cm under all the tree crops and in the grassland soils. A 500-gram sample of each soil originating from under each tree crop and the grassland were carefully packed into pre-labeled paper bags in triplicate (n=3) and sent to the laboratory for analysis of a selected number of primary and secondary macronutrients, micronutrients, and other soil parameters. The results showed N, K, Mg, Cu, Zn, and S were generally deficient in the sandy soil. A tree crop-specific soil organic matter, organic carbon, carbon stock contents, and water holding capacity measured were high under rubber and cocoa only. The variation in pH, electrical conductivity, bulk density, total porosity, and particle composition were generally similar except that the sand composition was lower in the soils under rubber and oil palm.